2021
DOI: 10.1186/s12883-021-02285-7
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and prognostic values of optic nerve sheath diameter and optic nerve sheath diameter/eyeball transverse diameter ratio in comatose patients with supratentorial lesions

Abstract: Background The optic nerve sheath diameter (ONSD) and ONSD/eyeball transverse diameter (ETD) ratio have been proven to be correlated with intracranial pressure. This study aimed to evaluate the prognostic roles of ONSD and the ONSD/ETD ratio in comatose patients with supratentorial lesions and to determine the relationship of these two indices with the prognosis of such patients. Methods A total of 54 comatose patients with supratentorial lesions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In addition, while ONSD alone tends to have a sizable overlap between the confidence intervals of “normal” and “elevated” ICP, ONSD‐ETD ratio did not, suggesting higher precision 59,61–64 . ONSD‐ETD ratio also had higher sensitivity and specificity for the prediction of poor neurological outcomes in patients with supratentorial injuries 65 . Two studies compared the accuracy of ONSD‐ETD ratio to ONSD alone in the detection of elevated ICP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while ONSD alone tends to have a sizable overlap between the confidence intervals of “normal” and “elevated” ICP, ONSD‐ETD ratio did not, suggesting higher precision 59,61–64 . ONSD‐ETD ratio also had higher sensitivity and specificity for the prediction of poor neurological outcomes in patients with supratentorial injuries 65 . Two studies compared the accuracy of ONSD‐ETD ratio to ONSD alone in the detection of elevated ICP.…”
Section: Discussionmentioning
confidence: 99%
“…59,[61][62][63][64] ONSD-ETD ratio also had higher sensitivity and specificity for the prediction of poor neurological outcomes in patients with supratentorial injuries. 65 Two studies compared the accuracy of ONSD-ETD ratio to ONSD alone in the detection of elevated ICP. One study ICP showed insufficient discriminative accuracy in detecting elevated ICP between the two measurements.…”
Section: Other Identified Parametersmentioning
confidence: 99%
“…The mortality noticeably increased in comatose patients with acute stroke when the ONSD was > 5.0 mm or the ONSD/ETD ratio was > 0.25[ 15 ]. Our previous study indicated that ONSD > 6.4 mm or ONSD/ETD ratio > 0.25 predicted the poor prognosis of comatose patients with supratentorial lesions[ 21 ]. The ONSD/ETD ratio was negatively correlated with glasgow outcome scale score ( r = -0.64)[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strong correlation between ONSD and ETD ( 12 ), the ONSD/ETD ratio has been introduced as a surrogate metric of ONSD accounting for interindividual variability due to orbit size ( 13 , 21 ). Several researches have reported that changes in the ONSD/ETD ratio are more effective than ONSD in detecting increased ICP ( 13 , 14 , 22 , 23 ). Albert et al ( 24 ) found that an ONSD of more than 5.25 mm and an ONSD/ETD ratio of more than 0.232 on initial CT may identify MCA stroke patients at high risk of developing malignant MCA syndrome.…”
Section: Discussionmentioning
confidence: 99%